Reputation and foreclosure with vertical integration: Experimental evidence - Claudia Möllers (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Building on the seminal paper of Ordover, Saloner and Salop (1990), I study the role of reputation building on foreclosure in laboratory experiments. In one-shot interactions, upstream firms can choose to build a reputation by revealing their price history to the current upstream competitor. In particular, integrated firms can establish a reputation to foreclose the input market.an outcome that would otherwise not be tenable due to a commitment problem. I get three main results: First, withdrawal from the input market is three times more common with reputation building of the integrated firm. Second, the anticompetitive effects are much stronger when the integrated firm builds a reputation. Third, integrated firms choose to build a reputation significantly more often than non-integrated firms. Markets with reputation building of the integrated firm are ten times more often monopolized than without.
Keywords: L42; D43; C90; D83; C72; 330; vertical restraints; commitment; reputation; experiments